2015
DOI: 10.2135/cropsci2014.04.0318
|View full text |Cite
|
Sign up to set email alerts
|

Nondestructive Measurements of Cottonseed Nutritional Trait Diversity in the U.S. National Cotton Germplasm Collection

Abstract: Recent studies have suggested that cottonseed (Gossypium spp.) has the potential to contribute to the effort against world hunger, particularly by providing a high‐quality protein source. This report analyzed the diversity in protein content and other seed quality factors in the U.S. National Cotton Germplasm Collection. Nine genomes (one tetraploid and eight diploid) and 33 species (five tetraploid and 28 diploid) were surveyed in this examination of 2256 accessions. A novel nondestructive nuclear magnetic re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

8
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(36 citation statements)
references
References 24 publications
8
28
0
Order By: Relevance
“…Collectively, most studies suggest a relatively strong, negative relationship between seed protein and oil (Hinze et al, 2015;Kohel and Cherry, 1983). This negative relationship is similar to what has been reported in other oilseeds (Blumenthal et al, 2008).…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Collectively, most studies suggest a relatively strong, negative relationship between seed protein and oil (Hinze et al, 2015;Kohel and Cherry, 1983). This negative relationship is similar to what has been reported in other oilseeds (Blumenthal et al, 2008).…”
supporting
confidence: 79%
“…Recently, Horn et al (2011) developed a new, nondestructive, low-field 1 H time-domain nuclear magnetic resonance (TD-NMR) method to allow for rapid measurement of seed protein and oil. Using this approach, Hinze et al (2015) surveyed the seed protein and oil content of 2256 accessions representing 33 species (five tetraploid and 28 diploid) from the US National Cotton Germplasm Collection. They found that protein content ranged from 10 to 36%, while oil content ranged from 8 to 27%.…”
mentioning
confidence: 99%
“…In Turner et al (1976), one cultivar, ‘Lockett 4789A’ (PI 529261), had a high seed‐oil correlation with seed index (0.74). Hinze et al (2015) also measured significant correlation between oil and seed index (0.45) among G. hirsutum accessions in the NCGC.…”
Section: Resultsmentioning
confidence: 79%
“…Hinze et al (2015) and Kohel (1978) have documented the existence of extensive genetic diversity for seed oil content in the US National Cotton Germplasm Collection (NCGC). In a survey of nine genomes and 33 species within the NCGC, Hinze et al (2015) noted that most of the variability for seed oil can be found within the commercial tetraploid species G. hirsutum and G. barbadense L.; therefore, making higher seed oil content relatively easy to introduce into cotton breeding programs. Kohel (1978) compared wild and improved G. hirsutum genotypes from the NCGC for seed oil content and also concluded that sufficient variability existed for seed quality improvement.…”
mentioning
confidence: 99%
See 1 more Smart Citation